Breeding status of Merlins Falco columbarius in the UK in 2008 - Ewing, Steven R; Rebecca, Graham W; Heavisides, Alan; Court, Ian R; Lindley, Patrick; Ruddock, Marc; Cohen, Simon; Eaton, Mark A (Bird study, 2011)
Capsule The third national Merlin survey estimated a UK population of 1162 breeding pairs (95% CI: 891–1462).Aims To estimate the number of breeding Merlins (with associated 95% confidence intervals) in the UK and the four countries (Scotland, England, Wales and Northern Ireland), and to compare these with the relevant estimates from the 1993–94 Merlin survey. In addition, to calculate estimates of change for several regional populations with complete survey coverage during both national surveys.Methods A subset of 10-km squares (Raptor Study Group squares and randomly sampled squares) was surveyed across the breeding distribution of Merlins in the UK using standardised methods devised during the 1993–94 national survey.Results The population estimate for Merlins in the UK was 1162 breeding pairs, and in Britain was 1128 pairs (95% CI: 849–1427), which although 13% lower, was not significantly different from the British estimate of the 1993–94 survey. Scotland held the bulk (733 pairs) of the UK Merlin population, and smaller numbers of 301 pairs, 94 pairs and 32 pairs were estimated for England, Wales and Northern Ireland, respectively. The population estimate for Wales may have been biased upwards by low coverage in the south of the country. Marked declines were noted in several regional Merlin populations, particularly in areas of northern England.Conclusions The 2008 Merlin survey suggests that the population in Britain has remained relatively stable since 1993–94, but with local declines, particularly in northern England. Currently, little is known about important drivers of regional population change in Merlins, but changes in land-use, prey populations and climate are likely to be important factors.